Long period fiber gratings in anti-resonant hollow core fiber - Ligang Huang; Yanxiang Zhao; Yujia Li; Shunli Liu; Hailin Zhou; Lei Gao; Leilei Shi; Guiyao Zhou; Tao Zhu (Applied Physics Express)
Long period gratings, based on anti-resonant hollow core fibers (AR-HCFs), are fabricated using a high-frequency CO _2 laser pulse by carving periodic grooves. This device exhibits both axial strain and bending sensing characteristics. Benefiting from the low thermal sensitivity and radiation resistance characteristic of AR-HCFs, this grating can be utilized in extreme environments, particularly in the high-radiation environment, such as nuclear power plants and space shuttles. Additionally, due to the characteristics of AR-HCFs, including low latency, low dispersion, low nonlinearity, and high damage threshold, this device also serves for long-distance fiber communication and high-power laser pulse shaping.